2012
DOI: 10.1007/s10916-012-9849-8
|View full text |Cite
|
Sign up to set email alerts
|

COSARA: Integrated Service Platform for Infection Surveillance and Antibiotic Management in the ICU

Abstract: The Intensive Care Unit is a data intensive environment where large volumes of patient monitoring and observational data are daily generated. Today, there is a lack of an integrated clinical platform for automated decision support and analysis. Despite the potential of electronic records for infection surveillance and antibiotic management, different parts of the clinical data are stored across databases in their own formats with specific parameters, making access to all data a complex and time-consuming chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The graphical interface allows the user to label infectious episodes during daily clinical rounds and interdisciplinary staff meetings to a predefined list of diagnoses in all patients admitted to the ICU. As such, the program facilitates the build-up of an extensive data-warehouse on antibiotic use and infection in the ICU [12]. During the study period treating physicians were not guided in the choice of the empirical antimicrobial by treatment algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…The graphical interface allows the user to label infectious episodes during daily clinical rounds and interdisciplinary staff meetings to a predefined list of diagnoses in all patients admitted to the ICU. As such, the program facilitates the build-up of an extensive data-warehouse on antibiotic use and infection in the ICU [12]. During the study period treating physicians were not guided in the choice of the empirical antimicrobial by treatment algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…Another example is the COSARA platform [24], which is focused on infection surveillance in ICUs. It provides functionalities for the automatic integration of clinical data and clinical decision support and alerts to alarming trends, among others.…”
Section: Decision Support In the Context Of Antimicrobial Resistancementioning
confidence: 99%
“…130 Several electronic surveillance systems have been developed to integrate resistance data, rate of nosocomial infection, quantity and quality of antibiotic usage. [131][132][133] These longitudinal data collections are not only a time-consuming job, but also require adequate insight to analyze, interpret, and formulate conclusions and possible working points. Fortunately, evidence has shown that this kind of analysis is capable of investigating prescription patterns and subsequent formulation of ASP goals.…”
Section: Clinical Decision Support Systems Are Useful Adjuncts In Aspmentioning
confidence: 99%